1886 Ga. Laws 26, 28, ch. 101 - (:unkn) unknown (General Publisher, 1886)
Required disclosure of guns, pistols, Bowie knives, and "such articles" for property tax purposes.
--
Keywords: TAX - PROPERTY OR SALES